Surface modification of acid-functionalized mesoporous gamma-alumina for non-fission 99Mo/99mTc generator. (September 2022) - Marlina,; Sarmini, E.; Lestari, E.; Pratama, C.; Nurmanjaya, A.; Sriyono,; Abidin,; Triyatna, F.; Kadarisman,; Aries, A.; Febriana, S.; Setiawan, H.; et al.
Abstract: Mesoporous gamma-alumina (MGA) was synthesized for neutron-activated 99 Mo adsorbent. Acid functionalization of the MGA was carried out to enhance the Mo adsorption capacity and the 99 Mo breakthrough profile. The acid-treated MGA has a more positive particle charge, rougher surface, smaller particle and pore size, larger surface area, and wider pore distance. The acid-treated MGA has a Mo adsorption capacity of 82.8 ± 6.3 mg Mo/g and resulted in 99m Tc eluate with the 99 Mo breakthrough at the acceptable level. Highlights: Surface modification of acid functionalization mesoporous gamma-alumina as a high-capacity adsorbent have been prepared Acid functionalization was carried out by soaking the mesoporous gamma-alumina with 0.5M nitric acid solution. Surface modification acid-functionalized mesoporous gamma-alumina enhanced the Mo adsorption capacity. The 99 Mo/ 99m Tc generator developed using the acid-functionalized gamma-alumina resulted in the qualified 99m Tc solution.